Efeitos da concentração de black carbon na radiação e emissividade atmosférica do Pantanal Mato-Grossense - Santos, Thamiris Amorim dos (2024)
The Pantanal is one of the largest wetland systems in the world and plays a significant role in local biodiversity and ecosystem. However, the increasing deforestation and wildfires in the region have become one of the main sources of atmospheric aerosol emissions in the area. Black Carbon is an aerosol that has the ability to absorb sunlight, contributing to atmospheric warming and altering the Earth-atmosphere radiation balance. The research aimed to analyze the effects of Black Carbon (BC) concentrations on the scattering and absorption capacity of Global Radiation (Rg), Net Radiation (Rn), and Atmospheric Emissivity (E) in the Pantanal region of Mato Grosso. Data were collected from a micrometeorological tower located at the Pantanal Research Advanced Base (BAPP) of the Federal University of Mato Grosso (UFMT), on Bahia das Pedras Farm, in the Private Natural Heritage Reserve (RPPN) SESC in the municipality of Poconé - MT between the years 2017 and 2019. Statistical analysis of the data involved the application of linear regression and the Co-spectrum method used to analyze specific events and seasonal patterns. The results indicate a significant influence of Black Carbon with concentrations above 0.10 μm³ on meteorological variables. During the period covered, a reduction in Rg and Rn was observed, resulting in the heating of atmospheric layers. It was also found that at high concentrations, BC causes Atmospheric Emissivity to decrease. In the Co-spectrum analysis, there was an increase in the influence or interdependence between variables over a 1-year period. The research highlights the importance of considering BC as a relevant component in discussions about climate change and interactions between aerosols and micrometeorological variables in the Pantanal.